Isolation and molecular characterization of Shewanella sp. G5, a producer of cold-active β -D-glucosidases - Cristobal, Hector Antonio (2008)
β ‐Glucosidase is a highly desired glycosidase, especially for hydrolysis of glycoconjugated precursors in musts and wines for the release of active aromatic compounds. A Shewanella sp. G5 strain was isolated from the intestinal content of benthonic organism (Munida subrrugosa) from different coastal areas of the Beagle Channel, Tierra del Fuego (Argentina). This marine bacterium was able to grow at a temperature range between 4 to 20 °C using different β ‐glycoside substrates, such as cellobiose, as carbon source. In this work, the Shewanella sp. G5 strain exhibited high β ‐glucosidase activity on plate at low temperature (4 and 20 °C). Two genes encoding different cold‐active β ‐glucosidases were amplified and sequenced and the nucleotide sequences were submitted to the GenBank. 16S rDNA and gyrB gene sequences were used for the molecular characterization of Shewanella sp. G5.